DESIGN OF OFF STREET PARKING FACILITIES ON PASAR TANJUNG – JEMBER DISTRIC - Dewi, Rizki Hippriyanti; Hayati, Nunung Nuring; Hasanuddin, Akhmad (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The PasarTanjung parking problems at Jember makes width effectivity of the street reduced, because of most the activities of the parking and unloading occurs On Street Parking. With 24,970 m2 of area of  PasarTanjung, its only have 1,569 m2 area of motorcycle parking and 63 m2 area of  the goods transportation . This study has function to planning the location of parking in the PasarTanjung in order to accommodate the vehicles and unloaded goods. Determination spacious parking requirements based on the arrival and departure of vehicles methods and based on the floor area of the building. The methods that have the biggest needed area waschoosen. The results of the analysis show that the method is based on the floor area of the building resulted in the largest total parking demand that is 7,101.5 m2. Determination of the location of off-street parking is planned at Tanjung Market building floor area of 11,400 m2. The division obtained 344 vehicle parking area for motorcycles, passenger cars 174 vehicles, 244 cars of freight vehicles. Other parking locations for motorcycle parking is in an existing park (Area 1) the number of 379 vehicles with a land area of 840 m2 parking , and Location 3 as much as 780 vehicle parking lot with a land area of 1,638 m2 .